Calculation and Simulation of Evapotranspiration of Applied Water - Richard L Snyder; Shu Geng; Morteza Orang; Sara Sarreshteh (Journal of Integrative Agriculture, 2012)
The University of California, Davis and the California Department of Water Resources have developed a weather generator application program “SIMETAW” to simulate weather data from climatic records and to estimate reference evapotranspiration (ETo) and crop evapotranspiration (ETc) with the generated simulation data or with observed data. A database of default soil depth and water holding characteristics, effective crop rooting depths, and crop coefficient (Kc) values to convert ETo to ETc are input into the program. After calculating daily ETc, the input and derived data are used to determine effective rainfall and to generate hypothetical irrigation schedules to estimate the seasonal and annual evapotranspiration of applied water (ETaw), where ETaw is the net amount of irrigation water needed to produce a crop. In this paper, we will discuss the simulation model and how it determines ETaw for use in water resources planning.